Military necessity civil-military relations in the Confederacy - Escott, Paul D. (U.S. civil-military relations, 2006)
Never before or since in American history have the needs and influence of the military weighed so heavily on society. Escott analyzes the militarization of life in the Confederacy and probes the relationships between military commanders, legislators, and Jefferson Davis and his administration. As the South struggled to wage an exhausting war against the North, military necessity increasingly determined policy and shaped all aspects of life. The military had an increasingly large impact not only on policy but also on events inside civil society. Military men played important roles in bringing about extensive social change, enforcing law and order, and placing significant restrictions on individual freedoms.